On the time trends among school-aged children in the Nordic countries. (30th September 2020) - Löfstedt, P; Arnarsson, A M; Corell, M; Lyyra, N; Madsen, K R; Torsheim, T; Thorstensson, E B; Välimaa, R; Damsgaard, M T; Eriksson, C
Abstract: Long-term trends in mental health of school-aged children can be analysed in the HBSC study. In Sweden the proportion of the children that report at least two weekly health complaints during the last six months has increased from the first data collection 1985/1985 to the latest 2017/2018 among all age groups for both girls and boys. Among the 11-year-old it reached 41 % among girls and 30 % boys, and among 15-year-old girls 62 % and boys 35 %. Can we trust this? The prevalence of two or more weekly health complaints showed large differences by country over time and especially in 2014, when Iceland and Sweden showed an almost 10%-point larger prevalence of multiple weekly symptoms (about 35%) than Denmark, Finland and Norway (about 25%). Norway was the only country to show a decline during 2002-2014. The prevalence of sleep difficulties has increased over the 12-year period in Denmark, Iceland, and Finland. In Sweden the prevalence fell from 26% to 21% from 2002 to 2006 but rose by 10% points from 2010 to 2014. Only Norway showed a positive development over the 12-year period; the prevalence declined in 2014 to 17% the lowest prevalence of sleep difficulties in any of the five Nordic countries. The trend of excellent self-rated health for Nordic adolescents indicates a small overall improvement between 2002 and 2006 but a stable trend in the following periods up until 2014. Finland and especially Sweden shows a decline in the prevalence of students having an excellent self-rated health. The only country to show a positive development in the prevalence of students having excellent self-rated health from 2002 to 2014, is Norway. The overall prevalence of adolescents having high life satisfaction has declined in most of the Nordic countries examined.